Identification of dentinogenic cell-specific surface antigens in odontoblast-like cells derived from adult dental pulp - Kyung-Jung Kang; Chun-Jeih Ryu; Young-Joo Jang (Stem Cell Research & Therapy, 2019)
Abstract Background Odontoblast is a unique progenitor that plays a role in dentin formation. So far, the dentinogenic differentiation of dental pulp stem cells and the role of surface molecules of odontoblasts in dentinogenesis are not well known yet. In this study, we obtained odontoblast-like cells from human dental pulp cells and screened odontoblast-specific cell surface antigens by decoy immunization. Methods Through decoy immunization with intact odontoblast-like cells derived from human dental pulp cells, we constructed 12 monoclonal antibodies (mAbs) of IgG type, and their binding affinities for cell surface of odontoblast-like cells were analyzed by flow cytometry. Immunoprecipitation, mass spectrometry, and immunohistochemistry were performed to demonstrate odontoblast-specific antigens. Odontoblasts were sorted by these mAbs using magnetic-activated cell sorting system, and their mineralization efficiency was increased after sorting. Results We constructed 12 mAbs of IgG type, which had a strong binding affinity for cell surface antigens of odontoblast-like cells. In human adult tooth, these mAbs accumulated in the odontoblastic layer between dentin and pulp and in the perivascular region adjacent to the blood vessels in the pulp core. Cell surface expression of the antigenic molecules was increased during odontogenic cytodifferentiation and decreased gradually as dentinogenic maturation progressed. Proteomic analysis showed that two representative antigenic molecules, OD40 and OD46, had the potential to be components for cell adhesion and extracellular matrix structures. Conclusion These results suggest that mAbs will be useful for detecting and separating odontoblasts from the primary pulp cells and other lineage cells and will provide information on the structures of extracellular matrix and microenvironment that appears during the dentinogenic differentiation.